Preventable and mitigable adverse events in cancer care: Measuring risk and harm across the continuum. Issue 23 (17th August 2017) - Lipitz‐Snyderman, Allison; Pfister, David; Classen, David; Atoria, Coral L.; Killen, Aileen; Epstein, Andrew S.; Anderson, Christopher; Fortier, Elizabeth; Weingart, Saul N.
Abstract : BACKGROUND: Patient safety is a critical concern in clinical oncology, but the ability to measure adverse events (AEs) across cancer care is limited by a narrow focus on treatment‐related toxicities. The objective of this study was to assess the nature and extent of AEs among cancer patients across inpatient and outpatient settings. METHODS: This was a retrospective cohort study of 400 adult patients selected by stratified random sampling who had breast (n = 128), colorectal (n = 136), or lung cancer (n = 136) treated at a comprehensive cancer center in 2012. Candidate AEs, or injuries due to medical care, were identified by trained nurse reviewers over the course of 1 year from medical records and safety‐reporting databases. Physicians determined the AE harm severity and the likelihood of preventability and harm mitigation. RESULTS: The 400‐patient sample represented 133, 358 days of follow‐up. Three hundred four AEs were identified for an overall rate of 2.3 events per 1000 patient days (91.2 per 1000 inpatient days and 0.9 per 1000 outpatient days). Thirty‐four percent of the patients had 1 or more AEs (95% confidence interval, 29%‐39%), and 16% of the patients had 1 or more preventable or mitigable AEs (95% confidence interval, 13%‐20%). The AE rate for patients with breast cancer was lower than the rate for patients with colorectal or lung cancer ( P ≤ .001). The preventable or mitigable AE rate was 0.9 per 1000 patient days. Six percent of AEs and 4% of preventable AEs resulted in serious harm. Examples included lymphedema, abscess, and renal failure. CONCLUSIONS: A heavy burden of AEs, including preventable or mitigable events, has been identified. Future research should examine risk factors and improvement strategies for reducing their burden. Cancer 2017;123:4728‐4736 . © 2017 American Cancer Society . Abstract : This study assesses the nature and extent of adverse events among cancer patients across inpatient and outpatient settings. A heavy burden of adverse events is identified, and this highlights opportunities for oncology clinicians to think more broadly about oncology‐related harm.